Endogean and Cavernicolous Coleoptera of the Balkans. XXIII. A new species of Paramaurops J. Müller (Coleoptera: Staphylinidae: Pselaphinae) from Greece - Hlaváč, Peter; Baňař, Petr; Davranoglou, Leonidas-Romanos; Kempton, James (Zootaxa, 2021)
We describe and illustrate a new species of pselaphine beetles, Paramaurops zagoricus sp. n., from the Zagori region of Epirus, Greece. A list summarising the distribution of Amauropini known from Greece is also provided.